Hypomethylation of the p53 and p16 suppressor genes in cellular aging - Kadirova D.A.; Mirhamidova P.; Shakhmurova G.A.; Alimova R.A. (BIO Web of Conferences)
Protein p53, a product of p53 gene expression, protects the integrity of the genome throughout life and promotes the cell repair in the process of cell aging. In this review, the fundamental significance of the p53 gene was analyzed in the cell aging. The review showed that hypomethylation of the promoter region of the p53 and p16 suppressor genes occurs during aging; the DNA hypomethylation is explained by the possible age-related decrease in the content of CH3-groups donor (S-adenosyl monophosphate) in the cell, and by the activity of DNA methyltransferases.